A Novel Radiofluorination Method for the Design of Rhenium(I) PET-Optical Hybrid Nuclear Medicines - Klenner, Mitchell Ashley (Curtin University, 2019)
Novel fluorine-18 labelled luminescent rhenium tricarbonyl complexes were synthesised to test their utility as agents for position emission tomography (PET) and optical hybrid imaging. These experiments lead to the discovery of a rhenium complexation-dissociation method, which produced never-before-seen radiotracers in substantial radiochemical yields that were unable to be radiosynthesised by traditional means. This method was further applied to the successful production of the Alzheimer’s disease PET imaging nuclear medicine, [18F]CABS13, and new analogues thereof.